2021
DOI: 10.1007/s10803-021-05148-9
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Mediated Interventions for Infants under 24 Months at Risk for Autism Spectrum Disorder: A Systematic Review of Randomized Controlled Trials

Abstract: Prodromal symptoms of Autism Spectrum Disorder (ASD) have been detected within the first year of life. This review evaluated evidence from randomized controlled trials (RCTs) of parent-mediated interventions for infants under 24 months who are at risk for ASD. Electronic databases, including grey literature, were searched up till November 2019. Seven RCTs were identified. There was substantial heterogeneity in recruitment, outcome measures and effect size calculations. Interventions did not reduce the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(358 reference statements)
0
5
0
Order By: Relevance
“…Therefore, various play-based interventions have been developed and used to support the social communication and language needs of autistic children [11][12][13][14][15][16][17][18][19]. Although many reviews and meta-analyses have reported the characteristics and overall effectiveness of play-based interventions on autistic children's social communication and language skills [39,51,[54][55][56][64][65][66][67][68][69][70][71][72][73], to the best of the authors' knowledge, the current study will be the first to evaluate the effectiveness of parent-mediated play-based interventions conducted in non-educational settings on the social communication and language skills of preschool autistic children. Hence, the review will shed new light on the role of parental mediation in the effectiveness of play-based interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, various play-based interventions have been developed and used to support the social communication and language needs of autistic children [11][12][13][14][15][16][17][18][19]. Although many reviews and meta-analyses have reported the characteristics and overall effectiveness of play-based interventions on autistic children's social communication and language skills [39,51,[54][55][56][64][65][66][67][68][69][70][71][72][73], to the best of the authors' knowledge, the current study will be the first to evaluate the effectiveness of parent-mediated play-based interventions conducted in non-educational settings on the social communication and language skills of preschool autistic children. Hence, the review will shed new light on the role of parental mediation in the effectiveness of play-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…comprehensive citation search of the previous systematic review and meta-analysis on parentmediated interventions in autism [39,51,[54][55][56][64][65][66][67][68][69][70][71][72][73]. The identified studies will be merged and downloaded into Mendeley Reference Manager software for performing the title, abstract and full-text screenings.…”
Section: Plos Onementioning
confidence: 99%
“…Since Phase I comprised the studies that were published between 2000 and January 2021, an additional search for relevant studies published in 2021 was also carried out on the aforementioned databases and by using the same search strings (see Table S1 traits of preschool autistic children (Althoff et al, 2019;Conrad et al, 2021;Dijkstra-de Neijs et al, 2021;Harrop, 2015;Kent et al, 2020;Law et al, 2021;Lee & Meadan, 2021;Liu et al, 2020;Nevill et al, 2018;O'Keeffe & McNally, 2021;Oono et al, 2013;Shalev et al, 2020;Trembath et al, 2019;Waddington et al, 2021). The identified studies from steps A and B were then merged and carried into the title and abstract screenings which were conducted by two authors, [ED & GF], to make sure no eligible study was overlooked.…”
Section: Phase Ii: Updatementioning
confidence: 99%
“…Like the early intervention literature of children with ASD, studies of parent mediated interventions for infants and young children at risk for ASD show mixed results (Feldman et al, 2022;Law et al, 2021;Yoder et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Like the early intervention literature of children with ASD, studies of parent mediated interventions for infants and young children at risk for ASD show mixed results (Feldman et al., 2022; Law et al., 2021; Yoder et al., 2021). Early intervention for at‐risk children may reduce ASD symptoms and subsequent diagnosis (Whitehouse et al., 2021) as well as improve core skills, such as child attentiveness (Jones et al., 2017), joint attention (Schertz et al., 2018), motor and vocal imitation (Azzano et al., 2022; Neimy et al., 2020; Yoder et al., 2021), and communication (Azzano et al., 2022; Bradshaw et al., 2017; Green et al., 2015; Rogers et al., 2014; Tanner & Dounavi, 2020; Yoder et al., 2021).…”
Section: Introductionmentioning
confidence: 99%